Cyberbullying in Media Social: A Mainstreaming the Victim Protection Principles in Indonesian Criminal Justice System - Abdiel Abraar Arya Aradhana; Charles Sahalatua Pangaribuan (Universitas Negeri Semarang, 2022)
The presence of the era of globalization presents a technological assistance in human life. It is also possible that the digitization process is used by irresponsible people to commit crimes in cyberspace or cybercrime. We often find that in the process of developing the virtual world there is also the development of new types of crime. The form of crime in question is cyberbullying or cyber bullying. In this article, the author will discuss the impact of cyber bullying, especially on children and the protection of victims of bullying in the Indonesian legal system, which in this case is related to the Bowo case. This study uses a normative juridical method with a statutory approach and an analytical approach by examining the contents of the law and discussing an analysis of the legal case being discussed regarding the act of bullying cyberbullying on social media in the Bowo case. Bowo received insults on social media related to his physical appearance or body shaming. The state has regulated in the ITE Law that forms of humiliation, threats and defamation in the scope of the use of technology such as social media can be criminally punished. The guarantee that victims are also protected by the state in the recovery process after a crime has occurred is regulated in the Republic of Indonesia Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 for the Protection of Witnesses and Victims.